Cheliped function in the porcellanid crab Petrolisthes japonicus: autotomy as an effective antipredator defence mechanism. Issue 1 (2nd January 2023) - Hamasaki, Katsuyuki; Fang, Yingdon; Dan, Shigeki
Abstract : Some porcellanid crabs (Decapoda Anomura) are known to escape predator crabs through a hair-trigger autotomy response when they are held by the cheliped only. The porcellanid crab Petrolisthes japonicus autotomizes chelipeds, and the post-autotomy cheliped movement functions like a lizard tail, which may increase predator distraction time, affording the prey more time to escape. However, the predatory encounters between prey and the relevant predators have not been observed to understand the benefits of autotomy in P. japonicus . The present study conducted 140 predation trials to evaluate the effectiveness of cheliped autotomy by P. japonicus in avoiding predation from its potential predator crab Gaetice depressus that commonly co-occurs with P. japonicus under cobble and boulders in intertidal zones. The predator attacked the prey in many trials (84%) and successfully grasped the prey in most attack cases (94%). The prey held by the body was able to escape the predator in a few cases (7%). When the prey was held by the cheliped only, the prey autotomized the cheliped and was able to escape the predator in many cases (75 and 83%, respectively), while the predator was eating the autotomized cheliped. The predator appeared to take a long time to handle the autotomized cheliped with its claws. Thus, our laboratory experiments demonstrated that P. japonicus exhibited high incidences of cheliped autotomy when it was held by the cheliped only, enabling it to escape the predator crab at high probabilities. Furthermore, post-autotomy movements may improve the efficacy of the antipredator defence mechanism of autotomized chelipeds in P. japonicus .